2014
DOI: 10.1542/hpeds.2013-0093
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Hospitalizations and Resource Utilization for Pediatric Pertussis

Abstract: BACKGROUND AND OBJECTIVE Pertussis is a serious and preventable childhood illness often necessitating hospitalization. The objective was to describe national trends in pediatric pertussis hospitalizations and resource utilization and factors associated with increased length of stay (LOS). METHODS This was a cross-sectional analysis of the 1997 to 2009 Healthcare Cost and Utilization Project Kids’ Inpatient Databases. We examined pediatric hospitalizations of children (0–18 years) with a diagnosis of pertussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…18 A cross sectional study on healthcare utilization after a respiratory transmittable disease outbreak reported a trend of increased medical resource use and hospitalization for publicly insured patients. 19 It is hypothesized that the trend of increased use of emergency services, particularly among young pediatric patients, is associated with the national health insurance service that covers all residents in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…18 A cross sectional study on healthcare utilization after a respiratory transmittable disease outbreak reported a trend of increased medical resource use and hospitalization for publicly insured patients. 19 It is hypothesized that the trend of increased use of emergency services, particularly among young pediatric patients, is associated with the national health insurance service that covers all residents in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Ad. Lutz 38 Brazil2010 Manual of laboratory diagnosisLaboratory diagnosisDescribes standards, routines and recommendations by the national reference laboratory Reish U 39 Germany2001 Experimental study113 Laboratory diagnosisRT-PCR technique showed high specificity and high predictive value Lopez MA 48 USA2014 Cohort1.012 Severe pertussisNeonates and children with chronic diseases are the most vulnerable groups, requiring hospitalizationSVS: Secretariat of Health Surveillance; MS: Ministry of Health; PCR: polymerase chain reaction; RT-PCR: real-time polymerase chain reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to specific antibiotic therapy, severe cases of pertussis require additional approaches to advanced life support to minimize complications 47 48 Hospitalization is determined by the risk of serious progression, and newborns and young infants should be considered as patients with pulmonary, muscular or neurological disease, in which complications are more frequent 6 8 , 25 , 29 , 47 , 48 Adequatehydration is essential for the fluidification of respiratory secretions and maintenance of blood volume 12…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations